2015
DOI: 10.3233/bmr-140487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected forms of physical activity on body posture in the sagittal plane in women post breast cancer treatment

Abstract: The diversity observed in the shape of anteroposterior spinal curvatures following physical training regimens of different type and nature demonstrates the need of appropriate exercise selection to attain the desired therapeutic outcome. Balanced postural changes were only identified among the women in the NW group. In the GE group, however, training only sustained the status existing prior to the initiation of the exercise regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In order to choose a physical exercise having complete efficacy against breast cancer treatment effects on the side of treatment, particular attention should be paid to Nordic Walking. Nordic Walking has been reported to achieve balanced postural changes in breast cancer-related treatment postural disorders10 ) , increases in upper extremity strength8 ) , improvements in cardio-metabolic and respiratory measures and has been used in the prevention and treatment of upper limb lymphedema. However, in order to elicit beneficial effects, it is necessary to perform the proper technique and achieve consistency in training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to choose a physical exercise having complete efficacy against breast cancer treatment effects on the side of treatment, particular attention should be paid to Nordic Walking. Nordic Walking has been reported to achieve balanced postural changes in breast cancer-related treatment postural disorders10 ) , increases in upper extremity strength8 ) , improvements in cardio-metabolic and respiratory measures and has been used in the prevention and treatment of upper limb lymphedema. However, in order to elicit beneficial effects, it is necessary to perform the proper technique and achieve consistency in training.…”
Section: Discussionmentioning
confidence: 99%
“…To furnish a wide-ranging healthy intervention, the recently introduced physical fitness discipline of Nordic Walking appears to be useful for breast cancer survivors. Nordic Walking is a form of brisk walking, utilizing a walking pole, which actively engages the trunk and upper limbs during walking, increasing their range of motion and increasing total body muscle endurance7,8,9,10 ) , and it has positive effects on cardio-metabolic, postural and balance measures in both healthy and pathological conditions11,12,13 ) . In addition, due to its principal characteristics, it is conceivable to consider Nordic Walking as an effective discipline against lymphedema14, 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The initial search resulted in the finding of 76 investigations. After reading the titles and the abstracts, 36 potential studies were identified, 9 of which were included in the final analysis (Figure ; Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Fields, Richardson, Hopkinson, & Fenlon, ; Fischer et al, ; Hanuszkiewicz, Malicka, Barczyk‐Pawelec, & Woźniewski, ; Hanuszkiewicz, Malicka, & Woźniewski, ; Jönsson & Johansson, , ; Malicka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The four RCTs analysed (Di Blasio, Morano, Bucci, et al, 2016b;Di Blasio, Morano, Napolitano, et al, 2016a;Fields et al, 2016;Malicka et al, 2011) showed a fair methodological quality (Table 1), while the five quasi-experimental studies (Fischer et al, 2015;Hanuszkiewicz et al, 2015Hanuszkiewicz et al, , 2014Jönsson & Johansson, 2009) obtained a score ranging from "fair" (Fischer et al, 2015;Jönsson & Johansson, 2014) to "poor" (18) ( Table 2).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…It is common to find studies that do not denote the position of evaluated inferior members clearly, such as the study of Batistão et al (2014), which requires the individuals to align their feet according to the width of their hip and the study of Hanuskiewicz et al (2015), that requires the individuals to stand freely with their feet in parallel and heels aligned. Both studies do not determine angles or distances between feet, which might be considered a lack of rigor in the protocol's methodology and produce misleading results in the evaluation.…”
Section: Raine (1994)mentioning
confidence: 99%